(untitled) (Sains Humanika, 2013)
This study aimed to validate the key elements of learning outcomes in terms of the perceptions of engineering students to improve the qualities of services of Higher Education Institutions (HEIs) particularly universities. This study involved 500 respondents from five selected HEIs in Malaysia. The instrument with a 7 level Likert scale was used to get the response. Overall, the questionnaire achieved a high level of reliability with Cronbach alpha values 0.967. The data obtained was processed through exploratory factor analysis (EFA) to observe the factors structure of learning outcomes. In addition, confirmatory factor analysis (CFA) was also conducted to validate the pre-determined contsructs. In conclusions, the findings from both analyses have identified and validated the two key elements in the learning outcomes of engineering students’ perception which are (i) the perceptions in technical knowledge and (ii) the perception in general knowledge.